Bioadditive rehabilitation with composite resins in severe wear: case report - Domínguez Díaz, Desirée (2019)
Tooth wear is the loss of hard tissue of multiple aetiology and may be due to functional or parafunctional factors. Depending on this, a restorative treatment should be chosen based on the severity of the wear, as it can result in loss of vertical dimension of occlusion (VOD), tooth sensitivity, and decreased quality of life. In these cases, the choice of restoration strategy must follow evidence-based treatment protocols, which include direct and indirect restoration techniques, as well as minimally invasive treatments based on composite resins that emerge as an alternative to conventional restorations of ceramics. This clinical case describes the treatment of a patient with severe dental wear through oral rehabilitation with composite resins through direct and indirect techniques, with the aim of preserving the tooth structure as much as possible and having greater aesthetic-functional predictability.